Дослідження ультрапериферійних зіткнень важких іонів на детекторі CMS установки CERN LHC Run 3 - Popescu, S. (Publishing house "Academperiodika", 2024)
Ultraperipheral collisions (UPCs) of heavy ions are a useful probe to study nuclear parton distribution functions (nPDFs) and, in particular, to characterize nuclear matter at Bjorken x < 10−3 and low squared momentum transfer Q2 (shadowing/saturation regime). In order to fully exploit these collisions, dedicated triggers on such event topologies were developed for the heavy ion data-taking period in 2023 by the CMS experiment. These triggers relied on the possibility of using the Zero Degree Calorimeter (ZDC) as a level-1 (L1) trigger detector for the first time. As a result, they allowed for an improved selection performance in addition to existing UPC triggers (as well as minimum-bias hadronic triggers), and enabled the study of hard processes (jets and heavy flavor hadrons) in photon-photon (γγ) and photon-nucleus (γN) scatterings [1].